Effects of Phytophthora sojae inoculation under flooded conditions on growth of soybean seedlings. (2nd October 2021) - Tada, Terufumi; Kato, Momo; Tanaka, Chihiro; Shiraiwa, Tatsuhiko
ABSTRACT: Phytophthora root and stem rot due to Phytophthora sojae is a major constraint of soybean production. This study evaluated the combined effect of P. sojae inoculation and flooding on growth of soybean seedlings. The soybean cultivar 'Enrei' was grown in a greenhouse in pots containing vermiculite and containers of field soil. The plants were inoculated with two P. sojae isolates and subjected to flooding. The ratio of dead to live plants ranged from 0 to 0.32 across all treatments. Pathogen inoculation caused a significantly shorter maximum root length (MRL) in all the three experiments. MRL and shoot and root dry weight were affected by interaction between inoculation and flooding in one experiment with vermiculite media. Flooding affected the growth parameters only in the experiment with soil media. The results indicated that root of the soybean seedlings that survived from P. sojae infection grew less well than the non-inoculated plants. Abstract : uf0001